The Impact of Business Support Services for Small and Medium Enterprises on Firm Performance in Low- and Middle-Income Countries : A Meta-Analysis - Cravo, Tulio A.; Piza, Caio (World Bank, Washington, DC, 2016)
Interventions designed to support small and medium enterprises are popular among policy makers, given the role small and medium enterprises play in job creation around the world. Business support interventions in low- and middle-income countries are often based on the assumption that market failures and institutional constraints impede the growth of small and medium enterprises. Significant resources from governments and international organizations are directed to small and medium enterprises to maximize their socioeconomic impact. Business-support interventions for small and medium enterprises in low- and middle-income countries most often relate to formalization and business environments, exports, value chains and clusters, training and technical assistance, and access to credit and innovation. Very little is known about the impact of such interventions despite the abundance of resources directed to small and medium enterprise business-support services. This paper systematically reviews and summarizes 40 rigorous evaluations of small and medium enterprise support services in low- and middle-income countries, and presents evidence to help inform policy debates. The study found indicative evidence that overall business-support interventions help improve firm performance and create jobs. However, little is still known about which interventions work best for small and medium enterprises and why. More rigorous impact evaluations are needed to fill the large knowledge gap in the field.